Reproduction in dogs part 1: surgical and non-surgical de-sexing options. (2nd August 2020) - Adams, Vicki J
Abstract : This article summarises the surgical and non-surgical options for desexing dogs, using standardised terminology by defining the meaning of commonly used terms. Desexing has been historically recommended to help with population control, disease prevention and behaviour modification. Surgical methods of gonadectomy are the most common method for desexing in both owned and unowned dogs, with orchiectomy being the most common method of desexing male dogs. Surgical methods of desexing in females may refer to ovariohysterectomy, ovariectomy, salpingectomy or hysterectomy with or without an ovarian autograft (referred to as a so-called 'ovary-sparing spay'). Non-surgical desexing methods include three broad categories: hormonal, immunological, and chemical or physical methods. The use of a gonadotropin-releasing hormone agonist as a method of inducing reversible infertility in dogs is discussed in detail, including a review of the physiological effects of surgical gonadectomy compared to a gonadotropin-releasing hormone agonist and potential health effects of each. There is a growing body of literature on the disease risks associated with whether a dog is intact or desexed, and by which method it has been desexed. This will be discussed in the next article.